Composite Photopolymerization: Temperature Increase According to Light Source and Dentin Thickness - Guenka Palma-Dibb, Regina; Savaris, Cristiane; Alexandra Chinelatti, Michelle; Augusto de Lima, Fabrício; Bachmann, Luciano; Jendiroba Faraoni, Juliana (Journal of Dentistry And Oral Implants, 2016)
When a composite resin restoration is photopolymerized, a considerable amount of heat can be produced, potentially causing pulpal injury. Objective: Evaluate the influence of the type of light source and remaining dentin thickness on the temperature increase in the pulp chamber while curing composite resin restorations. Material and Methods: Ninety-six tooth fragments obtained from bovine incisors were divided into groups/subgroups (n=12), according to the light source (LED and halogen light) and remaining dentin thickness (3.5, 3, 2, and 1mm). Class I cavities were prepared and restored with a composite resin. A temperature increase was obtained during photopolymerization of the adhesive and each composite increment. Data were analyzed using ANOVA and Fisher’s Test (α=5%). Results: LED promoted higher temperature increments when compared with the halogen light. Temperature levels were the lowest for 3.5mm-thick and the highest for 1mm-thick remaining dentin. Levels registered during the photopolymerization of each composite increment were superior for LED. Conclusions: Both light sources result in temperature increases above 5.5°C. Additionally, the remaining dentin thickness of 1mm promoted the largest temperature increase.
Keywords: Composite Resins; Dental Curing Lights; Dentin; Polymerization; Temperature.